The problem of simulation of microwave travelling wave process plant for drying timber - Tsekhmistro, R. I.; Omarov, М. А.; Orekhova, S. D. (Институт радиофизики и электроники им. А. Я. Усикова - научно-исследовательский институт Национальной академии наук Украины, 2011)
Physical aspects of modeling of the electromagnetic field capacity distribution in the microwave chamber for wood drying submitted to the passage of the running wave are presented. Refinements of the available electromagnetic models which make it possible to remove existing shortages are given. The numerical analysis of the electromagnetic field capacity distribution in equidistant array of Hertz radiators is carried out. The analysis of the Hertz electric dipole electromagnetic phase characteristics is given for the conducting medium equivalent to the timber pile.
The electrodynamic model of the timber drying process in a drying chamber where microwave heating is provided by the slotted-waveguide irradiators placed along the chamber, i.e., parallel to the lumber pile is considered in [1]. But the clear recommendations for designers and maintenance personnel of such process plants have not been received in full measure in spite of the physically rigorous statement of the problem, the use of the specialized computer simulation program and the experimental confirmation of the obtained results. The authors of the given work have tried to consider the solution of problems which would contribute to improvements in the available electrodynamic models and make an attempt to find a concrete algorithm for the microwave drying chambers computer-aided design.
Keywords: microwave chamber; shaped timber drying; heat power; local overheating; slotted‐waveguide irradiator; electromagnetic power distribution